Ask Question
31 March, 02:11

For the following system, tell which equation you would first use to solve for a variable in the first step of the substitution method. Explain your choice.

-2x + y = - 1

4x + 2y = 12

+3
Answers (1)
  1. 31 March, 03:33
    0
    start the solution either by solving the first given equati9on for y or by reducing the second equation by dividing all three terms by 2

    Step-by-step explanation:

    -2x + y = - 1 is most easily solvable for y: y = - 1 + 2x.

    Note that we can reduce the second equation to 2x + y = 6

    Substituting this - 1 + 2x for y in this new version of the second equation yields:

    2x + (-1 + 2x) = 6

    Simplifiying, we get:

    2x - 1 + 2x = 6, or 4x = 7. Then x = 7/4.

    Again: start the solution either by solving the first given equati9on for y or by reducing the second equation by dividing all three terms by 2.
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “For the following system, tell which equation you would first use to solve for a variable in the first step of the substitution method. ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers